Assessing exposure to weight stigma: development and initial validation of the Weight Stigma Exposure Inventory (WeSEI) - Kamolthip Ruckwongpatr; I-Hua Chen; Iqbal Pramukti; Po-Ching Huang; Janet D. Latner; Kerry S. O’Brien; Xuelian Wang; Jung-Sheng Chen; Servet Üztemur; Chien-Chin Lin; Yen-Ling Chang; Wei-Leng Chin; et al. (Journal of Eating Disorders)
Abstract Background Weight stigma is pervasive, and it has a significant impact on the social, physical, and psychological health of an individual. Weight stigma is observed from several different sources. Therefore, the present study developed and validated a new instrument, the Weight Stigma Exposure Inventory (WeSEI), to assess different sources of observed weight stigma across interpersonal and non-interpersonal sources. Methods The participants (n = 15,991) comprised Taiwanese young adults, Chinese adolescents, and Chinese young adults who completed paper-and-pencil and online surveys between September 2023 and December 2023. All participants provided demographic information, and completed the WeSEI, Weight Self-Stigma Questionnaire (WSSQ), and Perceived Weight Stigmatization Scale (PWSS). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to examine the factor structure of the WeSEI. Results EFA and CFA results confirmed a seven-factor structure (television sources, traditional media sources, social media sources, parent sources, stranger sources, significant other sources, and friends sources) across 35 items of the WeSEI. Moreover, the WeSEI was supported by measurement invariance across subgroups (i.e., subsamples, gender, and weight status). Moreover, there were positive correlations between all seven factors of the WeSEI and the WSSQ and PWSS. Conclusion The WeSEI appears to assess observed weight stigma from different sources, and had good reliability, validity, and invariance across various subsamples. The WeSEI may be useful in clinical practice and research for assessing exposure to weight stigma from different sources.